2017
DOI: 10.3390/md15030060
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Based Multifunctional Platforms for Local Delivery of Therapeutics

Abstract: Chitosan has been widely used as a key biomaterial for the development of drug delivery systems intended to be administered via oral and parenteral routes. In particular, chitosan-based microparticles are the most frequently employed delivery system, along with specialized systems such as hydrogels, nanoparticles and thin films. Based on the progress made in chitosan-based drug delivery systems, the usefulness of chitosan has further expanded to anti-cancer chemoembolization, tissue engineering, and stem cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…The percentage of glucosamine determines its physicochemical properties [15], of which the most notable is its cationic nature, and especially interesting if we consider that most natural polymers present neutral or anionic charges [16]. The mechanical properties of chitosan-based systems can therefore be modified by forming a polyelectrolyte complex with anionic compounds [17]. This polymer offers several advantages from a pharmaceutical point of view, as it is biocompatible and biodegradable [18].…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of glucosamine determines its physicochemical properties [15], of which the most notable is its cationic nature, and especially interesting if we consider that most natural polymers present neutral or anionic charges [16]. The mechanical properties of chitosan-based systems can therefore be modified by forming a polyelectrolyte complex with anionic compounds [17]. This polymer offers several advantages from a pharmaceutical point of view, as it is biocompatible and biodegradable [18].…”
Section: Introductionmentioning
confidence: 99%
“…The positive charge of CS NPs enables to bind negative charged biomolecules via electrostatic interaction. These properties have been used in several studies focused on several delivery systems including drugs, genes or nanoparticle delivery to the target tissues which is well described in many reviews [ 19 , 20 , 21 , 22 , 23 , 24 ]. Lee et al demonstrated the chemical conjugation of CD 7− specific single-chain antibody on the CS nanoparticle backbone useful for the delivery of siRNA into CD 4+ T cell lines [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…One appealing route of bio-application for this type of glycodynameric gels is related to precision, local medicine, and cancer targeting in particular. Multifunctional, responsive hydrogels with accessible formulation and controlled gelling time are primary candidates for injection at the tumor site if able to retain local spreading and acceptable toxicity [89,90]. In this context, the dynamic monoaldehyde strategy was used to build soft, 3D networks based on chitosan and nitrosalicylaldehyde for local tumor targeting [91].…”
Section: Glycodynameric Gels For Drug Deliverymentioning
confidence: 99%